MC Group Company Image Strategy In The Korean Drama “Graceful Family” - Fauzan, Rahil; Alfikri, Muhammad; Kamal, Aulia (Pena Cendekia Insani, 2022)
MC Group's Corporate Image Strategy in the Korean Drama Graceful Family. This study aims to see how the strategy is carried out in maintaining the company's image along with its weaknesses and advantages. The theory used is the theory of imaging the wish image. In the data analysis stage, the researcher uses a qualitative methodology and uses content analysis. By using content analysis techniques, the researcher tries to analyze the form of the imaging strategy used as the theoretical basis. Based on the findings on the object of research, the researcher draws conclusions. First, there are several imaging strategies described in the drama, namely, a) Forming public opinion by leading opinion by publishing articles on a regular basis. b) Manipulating the situation by changing the situation from a problem to something that seems normal, c) Negotiating by making an agreement that benefits both parties, d) Conducting a campaign to turn weaknesses into strengths, e) Constructing the image of the leadership by publishing achievements, f) Using the mass media Youtube as a medium for disseminating information, g) Conducting press conferences to straighten out negative public perceptions, g) Holding hearings with other leaders to evaluate company performance, h) Conducting field research before taking action, and i) Approaching emotional towards influential figures. Second, from the strategy carried out, the researcher found the weaknesses of the strategy used, namely, a) The existence of threats and coercion to the public, b) Giving bribes to other people, and c) Illegally extracting someone's personal information. In addition to finding weaknesses, there are several advantages that support the success of the strategy used, namely, a) There is harmony between work and areas of expertise, and b) Having access to reliable information control.